A QUANTITATIVE BIBLIOMETRIC ANALYSIS OF COST EFFICIENCY RESEARCH USING VOSVIEWER - Hafiza Huzaima Zukrova; Sri Andriani (CV. Denasya Smart Publisher, 2025)
This study aims to evaluate cost efficiency in the banking sector of selected Southeastern European countries and its impact on financial performance. The research employed a non-parametric approach using Data Envelopment Analysis (DEA) to measure cost efficiency and panel regression to analyze the factors affecting Return on Assets (ROA) and Return on Equity (ROE). Data were collected from the financial statements of commercial banks in Kosovo, Albania, North Macedonia, Bosnia and Herzegovina, Serbia, and Montenegro during the period 2010–2021. The findings revealed that the average cost efficiency among these countries was 79%, with North Macedonia showing the highest efficiency level. Panel regression analysis indicated that variables such as market share and loan-to-asset ratio had a significant positive impact on ROA and ROE, whereas cost efficiency and asset quality had a negative impact on ROA. These insights offer strategic value for stakeholders aiming to enhance operational efficiency and financial sustainability in the Southeastern European banking sector.